2020
DOI: 10.1186/s13019-020-01296-8
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors predict one-year mortality in patients with acute type-A aortic dissection

Abstract: Objective The goal of this study was to analyze perioperative risk factors to predict one- year mortality after operation for acute type A aortic dissection (AAD). Methods A total of 121 consecutive patients undergoing Stanford type A AAD surgery in Beijing Anzhen Hospital were enrolled. Preoperative clinical and laboratory data from patients were collected. Results Multivariable Cox regression analysis showed that significant factors associated with increased one-year mortality were elder age (year) (haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In this study, suspended red blood cell infusion was an independent risk factor for postoperative AKI in overweight ATAAD patients ( P = 0.015). This is consistent with previous research [ 25 , 26 ]. It may be related to postoperative ischemia–reperfusion injury in patients undergoing cardiopulmonary bypass surgery [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, suspended red blood cell infusion was an independent risk factor for postoperative AKI in overweight ATAAD patients ( P = 0.015). This is consistent with previous research [ 25 , 26 ]. It may be related to postoperative ischemia–reperfusion injury in patients undergoing cardiopulmonary bypass surgery [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Identifying preoperative predictors for poor outcomes is of utmost importance to stratify ATAD patients suitable for surgery. Previous study has identified several preoperative factors that predict poor outcomes in ATAD patients, 8 but EuroSCORE II was pointed out to be not accurate when applied for thoracic aortic dissection surgery. 9 And there was no preoperative risk evaluation system involving acute systemic inflammation factors for postoperative prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%